2006
DOI: 10.1128/mcb.01229-06
|View full text |Cite
|
Sign up to set email alerts
|

Small Interfering RNA Screens Reveal Enhanced Cisplatin Cytotoxicity in Tumor Cells Having both BRCA Network and TP53 Disruptions

Abstract: RNA interference technology allows the systematic genetic analysis of the molecular alterations in cancer cells and how these alterations affect response to therapies. Here we used small interfering RNA (siRNA) screens to identify genes that enhance the cytotoxicity (enhancers) of established anticancer chemotherapeutics. Hits identified in drug enhancer screens of cisplatin, gemcitabine, and paclitaxel were largely unique to the drug being tested and could be linked to the drug's mechanism of action. Hits ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
157
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 62 publications
4
157
0
Order By: Relevance
“…À HeLa cell line, also previously showed that the loss of SHFM1 or BRIP1 expression enhanced cisplatin cytotoxicity (26). Our study showed that the loss of either SHFM1 or BRIP1 expression increased oxaliplatin cytotoxicity in an siRNA screen by using the HCT 116 TP53 þ cell line.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…À HeLa cell line, also previously showed that the loss of SHFM1 or BRIP1 expression enhanced cisplatin cytotoxicity (26). Our study showed that the loss of either SHFM1 or BRIP1 expression increased oxaliplatin cytotoxicity in an siRNA screen by using the HCT 116 TP53 þ cell line.…”
Section: Resultssupporting
confidence: 75%
“…S2). Likely explanations for these differences include both the underlying mutational status of TP53 in the cell lines used and the more fundamental genomic variation between HeLa and HCT 116 tumor cell lines (derived from a human cervical adenocarcinoma and CRC, respectively), resulting in a differential sensitization upon the loss of additional genes in the presence of DNA-damaging agents such as cisplatin and oxaliplatin (26). Indeed, 11 genes that were previously identified as enhancers of cisplatin cyto-…”
Section: Resultsmentioning
confidence: 99%
“…Among 56 distinct siRNA transfections (54 single and 2 cotransfections), one siRNA species that depleted VDAC1 was consistently (in five out of five experiments) the most cytoprotective one. In this experimental setting, VDAC1 depletion was more efficient in maintaining viability and/or in inhibiting cell death than the knockdown of any other confirmed pro-apoptotic protein known to participate in CDDPelicited lethal signaling, including breast cancer 1 (BRCA1) (Bartz et al, 2006), p53 (Siddik, 2003), apoptotic peptidase-activating factor-1 , Bak and Bax (alone and in combination) (Wang et al, 2001;Kepp et al, 2007) as well as excision repair cross-complementing rodent repair deficiency, complementation group 1 (ERCC1) (Olaussen et al, 2006). VDAC1 knockdown exhibited greater cytoprotective effects against CDDP-induced cell death than the depletion of VDAC2 and VDAC3 (which were only marginally effective or totally ineffective, respectively) or of any other constituent of the PTPC such as the three adenine nucleotide translocase isoforms, the two hexokinase isoforms or cyclophilin D (all of which are implicated in CDDP-induced cell death) (Figure 1).…”
Section: Resultsmentioning
confidence: 97%
“…Notably, human cells expressing reduced levels of REV3L are more sensitive to killing by cisplatin (14,15). Additionally, in an siRNA-based screen, a reduction in REV3L sensitized human cells to killing by cisplatin to an extent equal or greater to a reduction of BRCA1 (16). Finally, chicken DT40 cells deficient in Rev3 showed the highest sensitivity to cisplatin of any of the DNA repair or checkpoint mutants tested (17).…”
mentioning
confidence: 97%